Finding the equilibrium real interest rate in a fog of policy deviations - John B. Taylor; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2016)
Recently there has been an explosion of research on whether the equilibrium real interest rate has declined, an issue with significant implications for monetary policy. A common finding is that the rate has declined. In this paper we provide evidence that contradicts this finding. We show that the perceived decline may well be due to shifts in regulatory policy and monetary policy that have been omitted from the research. In developing the monetary policy implications, it is promising that much of the research approaches the policy problem through the framework of monetary policy rules, as uncertainty in the equilibrium real rate is not a reason to abandon rules in favor of discretion. But the results are still inconclusive and too uncertain to incorporate into policy rules in the ways that have been suggested.
urn:nbn:de:hebis:30:3-402045
Keywords: 330